ANALISIS DAN PERANCANGAN TATA KELOLA TI MENGGUNAKAN COBIT 4.1 DOMAIN PLAN AND ORGANIZE DAN ACQUIRE AND IMPLEMENT: STUDI KASUS PT XYZ - Amanda Yunia Zafarina; Murahartawaty Arief; Rahmat Mulyana (Jurnal Sistem Informasi, 2016)
Companies that implement information technology should have the ability to manage the governance and the implementation of the Information Technology Governance (ITG). Application of IT Governance may support the organization in building a framework to direct and decide the utilization of IT according to the organization needs aligned with its vision, mission, values, strategy, and culture. Keputusan Minister of BUMN is the reference on good IT governance through its implementations in state-owned enterprises. According to the IT governance framework mentioned in PER-02/MBU/ 2013, COBIT 4.1 is a framework that focuses on the relationship between IT and enterprise business. Hence, in this research, COBIT (Control Objective for Information and Related Technology) 4.1 framework is used to analyze and design the IT governance. In the first phase, the maturity level is measured to analyze the maturity and gap level of the IT governance in PT. XYZ, i.e. using Plan and Organise (PO) and Acquire and Implement (AI) domains. In the next phase, the priority analysis is conducted. The result of the analysis is considered as essential and critical process take the next analysis, i.e. gap and risk analysis. Afterwards, the IT governance map is designed. The design includes policy, procedure, organization structure, technology recommendation, and processes priority related document template.